Childhood falls: characteristics, outcome, and comparison of the Injury Severity Score and New Injury Severity Score. Issue 7 (22nd June 2006) - Bulut, M; Koksal, O; Korkmaz, A; Turan, M; Ozguc, H
Abstract : Objectives: The aim of this study was to determine the general characteristics of childhood falls, factors affecting on mortality, and to compare the Injury Severity Score (ISS) and the New Injury Severity Score (NISS) as predictors of mortality and length of hospital stay in childhood falls. Methods: We retrospectively analysed over a period of 8 years children aged younger than14 years who had sustained falls and who were admitted to our emergency department. Data on the patients' age, sex, type of fall, height fallen, arrival type, type of injuries, scoring systems, and outcome were investigated retrospectively. The ISS and NISS were calculated for each patient. Comparisons between ISS and NISS for prediction of mortality were made by receiver operating characteristic (ROC) curve and Hosmer-Lemeshow (HL) goodness of fit statistics. Results: In total, there were 2061 paediatric trauma patients. Falls comprised 36 (n = 749) of these admissions. There were 479 male and 270 female patients. The mean (SD) age was 5.01 (3.48) years, and height fallen was 3.8 (3) metres. Over half (56.6%) of patients were referred by other centres. The most common type of fall was from balconies (38.5%), and head trauma was the most common injury (50%). The overall mortality rate was 3.6%. The cut off value for both the ISS and NISS in predicting mortality was 22 (sensitivity 90.5%, specificity 95.4% for ISS; sensitivity 100%, specificity 88.7% for NISS) (p>0.05). Significant factors affecting mortality in logistic regression analysis were Glasgow Coma Scale (GCS) <9, ISS >22, and NISS >22. There were no significant differences in ROC between three scoring systems. The HL statistic showed poorer calibration (p = 0.02 v p = 0.37, respectively) of the NISS compared with the ISS. Conclusions: In our series, the head was the most frequent site of injury, and the most common type of fall was from balconies. Scores on the GCS, NISS, and ISS are significantly associated with mortality. The performance of the NISS and ISS in predicting mortality in childhood falls was similar.